Multifocal motor neuropathy and visual pathway impairment: A case report - Keisuke Kido; Shinichi Wada; Yuwa Oka; Yuta Terada; Manabu Inoue; Toshiaki Hamano (Clinical Neurophysiology Practice, 2021)
Background: Multifocal motor neuropathy (MMN) occasionally presents with cranial nerve involvement. However, no MMN cases with visual pathway impairment demonstrated by visual evoked potential (VEP) have been reported. Case report: A 36-year-old man was admitted to our hospital with progressive muscular weakness. On admission, neurological findings revealed bilateral muscle weakness and atrophy of the distal upper limbs. The blood tests were positive for GM-1 ganglioside antibodies. Nerve conduction studies revealed bilateral conduction block in the median nerve. He was diagnosed with MMN. Intravenous immunoglobulin treatment improved muscle weakness and blurred vision, which was not a complaint when he was first seen. Moreover, VEP showed a post-treatment shortening of P100 latency. These treatment effects were consistently observed for 3.5 years. Significance: Our findings suggested that MMN could affect the visual pathway through autoimmune mechanisms.